Social Media, Mass Mobilization and National Development in Nigeria: Lessons from the #EndSARS Protest - Akpan, Eno-Obong Blaise; Targema, Tordue Simon (ASEAN Journal of Community Engagement, 2022)
This study explored the potential of social media for effective mass mobilization and community engagement to attain national development in Nigeria. Premised on the fact that social media have become popular platforms attracting millions of subscribers, the study examined how the opportunities they offer could be harnessed and purposefully deployed to galvanize the citizens to pursue national development causes. This was done against the backdrop of the technological determinism theory that provides the framework for investigating the indispensable role which technology plays in the advancement of a nation’s socio-economic development. The secondary research approach was adopted to carry out the study and studied the 2020 #EndSARS protest (SARS refers to Special Anti-Robbery Squad), a youth uprising that aimed to put an end to all forms of police brutality and systemic injustices in the country. This study examined the nature of digital activism that social media facilitated during the protest and how that translated into real-life activism, thereby galvanizing the youth to actively execute the protest. By considering the challenges of the platforms in this regard such as the possibility of being hijacked and negatively deployed in a counterproductive manner, the study concludes that proper mainstreaming of social media into the community engagement and national development struggle would help engage meaningfully with the citizens and mobilize them to attain socio-economic development in the country. Conclusively, the #EndSARS experience demonstrates that social media portends considerable opportunities to engage citizens positively for national development in Nigeria.